2020
DOI: 10.1002/em.22356
|View full text |Cite
|
Sign up to set email alerts
|

Isobutylparaben Negatively Affects Porcine Oocyte Maturation Through Increasing Oxidative Stress and Cytoskeletal Abnormalities

Abstract: As a member of parabens (PBs), Isobutylparaben (IBP) has a broad-spectrum antimicrobial activity and widely used in personal care products and cosmetics. Recent studies have indicated that usage of IBP poses a potential threat to reproductive health. In this study, we aimed to reveal the effects of acute exposure to IBP on the meiotic maturation of porcine cumulus oocyte complexes. Initial study showed that 200 μM of IBP significantly reduced the rate of the first polar body extrusion with no significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
12
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 52 publications
7
12
0
5
Order By: Relevance
“…We found that at concentrations of 750 and 1000 μ m , MePB altered oocyte cytoplasm, which may compromise the resumption of meiosis II. In this regard, our results are similar to those reported by Meng et al (2020), where they observed that IBP generated oocyte cytoplasm damage, specifically to the cytoskeleton, causing disturbances in actin microfilaments. It is known that PBs can produce different biological effects, such asinhibition in membrane transport and mitochondrial function (Soniet al, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found that at concentrations of 750 and 1000 μ m , MePB altered oocyte cytoplasm, which may compromise the resumption of meiosis II. In this regard, our results are similar to those reported by Meng et al (2020), where they observed that IBP generated oocyte cytoplasm damage, specifically to the cytoskeleton, causing disturbances in actin microfilaments. It is known that PBs can produce different biological effects, such asinhibition in membrane transport and mitochondrial function (Soniet al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, our study showed that MePB has low cytotoxicity on oocytes at the concentration ranges assayed. According to Meng et al (2020), the number of oocytes with apoptosis increased after IBP exposure; however, in another study, the toxic potential of PBs in hepatocytes was evaluated, and they determined that cytotoxicity is proportional to the size of PBs (Nakagawa & Moldeus, 1998). Therefore, the longer the carbon chain of PBs, the more their effect is exacerbated (Andersen, 2008;Soni et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that parabens negatively affected the female reproductive system by decreasing ovarian weight, follicle development, and pregnant maintenance [22]. Moreover, exposure to isobutylparaben during IVM disrupts oocyte maturation through cytoskeleton, ROS, and epigenetic modifications [23]. As BP has the most potent estrogenic effects among parabens, exposure to BP could be more harmful to the female reproductive system.…”
Section: Discussionmentioning
confidence: 99%